Vascular flora of Jelenovac Forest Park (Zagreb, Croatia) - Justić, Marta (Array, 2021)
A floristic study of Jelenovac Forest Park, located in Zagreb city centre, was conducted during the vegetation season of 2019. In total, 255 vascular plant taxa were recorded, divided into 75 plant families, of which Compositae (12.55%), Rosaceae (7.06%) and Poaceae (6.67%) are the most represented. The spectrum of life-forms indicates the dominance of hemicryptophytes (43.14%) and phanerophytes (27.45%). The chorological analysis shows a domination of Eurasian floral element (27.45%), followed by large share of widespread (22.35%) and cultivated and adventitious plants (18.04%). Only one threatened, three strictly protected and as many as 12 invasive plant taxa were found. Comparison of flora of Jelenovac with similar urban and suburban areas of Zagreb conglomeration yielded diverse results, but still reflecting the common biogeographical position and influence of temperate climate and indicating a comparatively high anthropogenic influence.